425 is decreased to 319.
The above statement means that a number should be deducted from 425 to get the difference of 319.
Let x be the unknown number.
425 - x = 319
425 - 319 = x
106 = x
106 is the unknown number.
It can be phrased like this: 425 decreased by 106 is 319.
Answer:
250 x 3 = 750g
750g is your final answer
Answer:
![5](https://tex.z-dn.net/?f=5)
Step-by-step explanation:
![1. \: 3 + 4 \times 3 \div 6 \\ 2. \: 3 + 12 \div 6 \\ 3. \: 3 + 2 \\ 4. \: 5](https://tex.z-dn.net/?f=1.%20%5C%3A%203%20%2B%204%20%5Ctimes%203%20%5Cdiv%206%20%5C%5C%202.%20%5C%3A%203%20%2B%2012%20%5Cdiv%206%20%5C%5C%203.%20%5C%3A%203%20%2B%202%20%5C%5C%204.%20%5C%3A%205)
Answer:
C. 0.98
Step-by-step explanation:
Let x be the mean of Company A and B annual profit and x/2 and y are standard deviation of Company A and B annual profit.
P(B<0) = 0.9*P(A<0)
P(Z<(0-x)/y) = 0.9*P(Z<(0-x)/(x/2))
P(Z<-x/y) = 0.9*P(Z<-2)
P(Z<-x/y) = 0.0205
x/y =2.04
Or y/x = 1 /2.05
y/x =0.49
Ratio of the standard deviation of company B annual profit to the standard deviation of company A annual profit =y/(x/2)
= 2*(y/x)
= 2*0.49
= 0.98
Answer:
The zeros of the function are;
x = 0 and x = 1
Step-by-step explanation:
The zeroes of the function simply imply that we find the values of x for which the corresponding value of y is 0.
We let y be 0 in the given equation;
y = x^3 - 2x^2 + x
x^3 - 2x^2 + x = 0
We factor out x since x appears in each term on the Left Hand Side;
x ( x^2 - 2x + 1) = 0
This implies that either;
x = 0 or
x^2 - 2x + 1 = 0
We can factorize the equation on the Left Hand Side by determining two numbers whose product is 1 and whose sum is -2. The two numbers by trial and error are found to be -1 and -1. We then replace the middle term by these two numbers;
x^2 -x -x +1 = 0
x(x-1) -1(x-1) = 0
(x-1)(x-1) = 0
x-1 = 0
x = 1
Therefore, the zeros of the function are;
x = 0 and x = 1
The graph of the function is as shown in the attachment below;